Urban development in Asia and Africa : geospatial analysis of metropolises - Murayama, Yūji, 1953-; Kamusoko, Courage; Yamashita, Akio; Estoque, Ronald C. (Springer, 2017)
This book examines the urban growth trends and patterns of various rapidly growing metropolitan regions in developing Asian and African nations from the perspective of geography. State-of-the-art geospatial tools and techniques, including geographic information system/science and remote sensing, were used to facilitate the analysis. In addition to the empirical results, the methodological approaches employed and discussed in this book showcase the potential of geospatial analysis, e.g. land-change modeling for improving our understanding of the trends and patterns of urban growth in Asia and Africa. Furthermore, given the complexity of the urban growth process across the world, issues raised in this book will contribute to the improvement of future geospatial analysis of urban growth in the developing regions. This book is written for researchers, academicians, practitioners, and graduate students. The inclusion of the origin and brief history of each of the selected metropolitan regions, including the analysis of their urban primacy, spatiotemporal patterns of urban land-use changes, driving forces of urban development, and implications for future sustainable development, makes the book an important reference for various related studies.
Includes index.
Keywords: Urbanization -- Asia.; Urbanization -- Africa.; Africa.; Asia.; elektronické knihy; electronic books